Making for learning: how graduate students discuss and design for maker-focused pedagogy. Issue 3 (15th May 2021) - Humburg, Megan; Tan, Verily; Maltese, Adam V.; Simpson, Amber; Danish, Joshua A.
Abstract : Purpose: This study aims to understand how graduate students in a maker education course discuss beliefs about making and implement these beliefs as pedagogy in their curricular designs. Design/methodology/approach: Interview transcripts from seven students were analyzed thematically for conceptions of making and learning. Lesson plans were also coded for elements of making, and the authors compared students' articulated ideas about making with the practical implementation of making in their designs. Findings: Students reflected on the nature of making and the possible benefits and tensions surrounding the use of making for learning. Multiple students discussed benefits for their future learning and careers. Comparisons between interview and lesson plans highlight both successful alignments and key gaps in the application of making principles, including struggles that students encountered when translating their beliefs about making into real-world pedagogy. Research limitations/implications: Given the limited sample size, future research should explore the extent to which educators in other contexts encounter similar or different obstacles in their development of maker-focused pedagogies. Practical implications: Findings can be used to inform future maker education courses to better support students in successfully translating core principles of making from general beliefs into effective and practical pedagogical strategies. Originality/value: Despite widespread interest in combining making with educational spaces, much remains to be understood about the strategies that educators use to integrate elements of making into their pedagogy. This study contributes discussions of the benefits and tensions that maker educators may encounter when blending tenets of making with the needs of formal education.